2021
DOI: 10.1021/acs.iecr.1c00423
|View full text |Cite
|
Sign up to set email alerts
|

Array Modified Molded Alumina Supported PdAg Catalyst for Selective Acetylene Hydrogenation: Intrinsic Kinetics Enhancement and Thermal Effect Optimization

Abstract: High temperature calcined spherical alumina material with macroporous structure is widely used in the typical strong exothermic industrial catalytic process due to its good heat transfer ability. Aiming at the problem that its low surface area limits the dispersion of active metals, an in situ growth method is applied to fabricate an alumina array on spherical alumina, while maintaining the heat transfer advantages. Taking the as-obtained modified alumina as support, a highly dispersed PdAg catalyst for select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…68 Consequently, these peaks are reasonably considered to be caused by the desorption of H 2 , in which the former at 300-330 C is assigned to the desorption of chemical adsorbed hydrogen, while the latter at 410 C is ascribed to the spillover of hydrogen. 69 Compared with other catalysts, the desorption peak over Pd/TiO 2 -HT300 shifts to lower temperature of 360 C. Moreover, the peak intensity of hydrogen spillover over Pd/TiO 2 -HT300 is the strongest among all samples. Therefore, it can be concluded that more V o contributes to the occurrence of hydrogen spillover to provide more active hydrogen species during the reaction process.…”
Section: Insight Into the Role Of V O Adjacent To Pd Speciesmentioning
confidence: 81%
“…68 Consequently, these peaks are reasonably considered to be caused by the desorption of H 2 , in which the former at 300-330 C is assigned to the desorption of chemical adsorbed hydrogen, while the latter at 410 C is ascribed to the spillover of hydrogen. 69 Compared with other catalysts, the desorption peak over Pd/TiO 2 -HT300 shifts to lower temperature of 360 C. Moreover, the peak intensity of hydrogen spillover over Pd/TiO 2 -HT300 is the strongest among all samples. Therefore, it can be concluded that more V o contributes to the occurrence of hydrogen spillover to provide more active hydrogen species during the reaction process.…”
Section: Insight Into the Role Of V O Adjacent To Pd Speciesmentioning
confidence: 81%
“…Pd-based-catalyzed C 2 H 2 selective hydrogenation is a typical example, which is crucial to reduce the trace (0.5–2%) of C 2 H 2 content in naphtha pyrolysis products to a level of ppm while retaining large amounts of C 2 H 4 . ,, The modification of Pd catalysts with Ag has been reported as an important way to improve the C 2 H 4 yield of C 2 H 2 semihydrogenation catalysts. To improve PdAg catalytic performance in C 2 H 2 selective hydrogenation, researchers have synthesized many PdAg catalysts with different surface structures, such as the core–shell structure and single-atom catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Since VIII metals such as Pd and Ni are strong in ethyne activation and IB metal-based catalysts are selective for ethylene formation, VIII-IB bimetallic catalysts have been widely constructed to achieve high ethyne conversion and high selectivity towards ethylene simultaneously. Pd-Ag, 20,[101][102][103][104][105][106][107][108][109][110][111][112][113] Pd-Au, 114,115 Pd-Cu, [116][117][118] Ni-Cu, 119 Pt-Cu, 120 Ni-Ag, 121 and Ni-Au (ref. 122) have been developed.…”
Section: ① Viii-ib Catalystsmentioning
confidence: 99%